A Practical Approach to Identify the Phases Sequence in Five Phase Machines with Combined Star–Pentagon Configuration - Kotb B. Tawfiq; Mohamed N. Ibrahim; Ayman M. EL-Refaie; Peter Sergeant (Mathematics, 2022)
Due to the significant advantages of a high torque density, better fault tolerance and high efficiency, the combined star–pentagon winding has recently gained researchers’ interest. In this paper, a simple method to identify the sequence of phases of a five-phase machine with combined star–pentagon winding was proposed. This was accomplished using resistance measurements between adjacent and non-adjacent phases. The analysis was conducted to clarify the phase sequence identification method. A case study of a 5.5 kW five-phase synchronous reluctance motor with combined star–pentagon winding was considered to simply apply the proposed method using an LCR meter for resistance measurements. The parasitic and wire resistances are dominant in the studied case, and this did not influence the accuracy of this method.